Modern Times 1970-99 The Eventful 20th Century - Reader's Digest (U.S.A Reader's Digest Associations, 2000)
The tragedies, triumphs, and trends of the last three decades of the 20th century come to life in a dazzling collage of pictures and incisive, compelling narration. From the rise of the personal computer to the fall of the Berlin Wall, here are the exciting final years of our eventful century.